Audiovisual Media Influence on Skills Writing Job Application Letter Class XII Students at SMAN 1 Pangkalan Lesung - Shinta Puspita Sari; Elvrin Septyanti; Silvia Permatasari (CV. Rayyan Dwi Bharata, 2023)
The emergence of problems of decreased learning activities and interest in students' writing skills is still low. This study discusses the influence of audiovisual media on the job application letter writing skills of grade XII students at SMAN 1 Pangkalan Lesung. The purpose of this study was to determine the influence of audiovisual media on job application letter writing skills in grade XII students at SMAN 1 Pangkalan Lesung. The benefits of research to develop learning media through appropriate educational methods so that they can influence student learning with potential and character. Research methods are obtained with pre-experimental designs, research instruments in the form of pretests and postes job application letter writing skills. Research data analysis techniques use descriptive statistical test techniques, normality tests, and homogeneity tests. The results of the study are audiovisual media affect the learning outcomes of job application letter writing skills for grade XII students at SMAN 1 Pangkalan Lesung, by giving the impression of a pleasant student learning experience, so that students become more motivated, learning becomes less boring, and makes communication easier to achieve effective and efficient learning goals.